MODERN CONCEPTS OF TREATMENT OF ENDOMETRITIS WITH CLINICAL APPLICATION OF PLATELET-RICH PLASMA IN THE FEMALE REPRODUCTIVE SYSTEM - Nazarova Zebiniso Yusufjonovna (World Scientific Research Journal, 2025)
Annotation: Platelet-rich plasma is an autologous plasma containing platelets prepared from fresh whole blood drawn from a peripheral vein. Through processing, it can be prepared to contain supraphysiologic levels of platelets at three to five times greater than the level of normal plasma. PRP has been explored both in vivo and ex vivo in the human endometrium model in its ability to harness the intrinsic regenerative capacity of the endometrium. Intrauterine autologous PRP infusions have been shown to increase endometrial thickness and reduce the rate of intrauterine adhesions. In the setting of recurrent implantation failure, intrauterine infusion of PRP has been shown to increase clinical pregnancy rate. PRP also appears to hold a potential role in select patients with premature ovarian insufficiency, poor ovarian responders and in improving outcomes following frozen–thawed transplantation of autologous ovarian tissue. Further studies are required to explore the potential role of PRP in reproductive medicine further, to help standardise PRP protocols and evaluate which routes of administration are most effective.